(untitled) (Psychology Travelogs, 2024)
The article notes that an important role in the empirical experiment is given to the study of personal readiness of future psychologists to provide psychological assistance. The structure of personal readiness of future psychologists to provide psychological assistance is presented. The following components of personal readiness to provide psychological assistance are distinguished: a) motivational (attitude, interest in the subject of activity, as well as other stable motives); b) orientation (knowledge and understanding of the peculiarities of the future specialty); c) operational (knowledge, skills, abilities, mastery of the processes of analysis, synthesis, comparison, generalization); d) volitional (self-control, ability to manage one’s own actions); e) evaluative (self-assessment of one’s readiness). The methods of studying the personal readiness of future psychologists to provide psychological assistance are presented. The results are analyzed. The cadets who are at risk are identified, namely: according to the motivational component - cadets who have made a situational choice of profession; according to the orientation component – cadets with a low level of professional awareness of future activities with different categories of clients; according to the operational component – cadets with a low level of development of empathy, reflexivity, tolerance, frustration tolerance, self-control; with a low level of development of the social and communicative sphere (have difficulties in social and professional interaction, difficulty switching in the communicative and professional sphere); by the volitional component – cadets with a low level of self-control in communication, rigidity, uncontrolled directness; by the evaluative component – cadets are not confident in their professional skills.